Manajemen Arsip Untuk Meningkatkan Pemeliharaan Arsip Statis Dinas Perpustakaan Dan Kearsipan Kabupaten Aceh Barat - Cut Intan Zahara; Mursyidin Mursyidin; Nellis Mardhiah; Zuhrizal Fadhil (Prodi Ilmu Pemerintahan, Universitas AMIKOM Yogyakarta, 2022)
This study aims to determine how to manage static archives in the Library and Archives Service of West Aceh Regency. This study uses a qualitative method with a descriptive approach. Data collection techniques in this study used the methods of observation, interviews, and documentation. The informants in this study were the Head of Archives and Archives. The results of this study indicate that the management of static archives in the previous year has not gone well and also has not received a list of static archives. This is because in the field of archives there is a lack of human resources as archivist functional staff who have the competence and skills in carrying out management and maintenance activities for archives.